Tingkatkan kualitas SDM koperasi pesantren melalui edukasi pembukuan dan pembuatan laporan keuangan - Mohamad Bastomi; M. Mahruz Ali. Hs (Universitas Pendidikan Indonesia (UPI), 2022)
Candidates for Undergraduate Service (KSM-Thematic) are a substitute for Real Work Lectures (KKN-PPM). It has been carried out since the Covid-19 pandemic which aims to provide students with experiences for the community. The major changes caused by the COVID-19 pandemic have resulted in people experiencing several new habits that must be accepted and carried out continuously. The experience of students so far is felt to be able to have a positive impact on the community. However, unlike KKN-PPM, this time the service is aimed at areas affected by the COVID-19 pandemic. The KSM-Thematic activities that have been carried out are 1) inviting male students and the community for community service, 2) distributing free masks to students and the community, 3) boosting the economy at the madinatul ulum Islamic boarding school by holding training for cooperative management, 4) majlis taklim routine sholawat and tahlil together and train fluency in reading the Qur'an by teaching TPQ. On the basis of the activities that have been carried out, the KSM-Thematic Islamic University of Malang has a stimulus to improve the cognitive, moral and social stages of students and the community of the madinatul ulum Islamic boarding school in Selowogo village.